Planning, income distribution, private foreign investment - Organisation for Economic Co-operation and Development (Paris : Development Centre of the Organisation for Economic Co-operation and Development ; [Washington, D.C. : sold by the OECD Publications Center], 1974)
The International Meeting of Directors af Development Research and Training Institutes, which took place in Belgrade was organised by the OECD Development Centre with the co-sponsorship of the Development Research of the IBRD and of the Belgrade Centre of Investment Research
Includes bibliographical references.
osc 21/09/2021
Loans
Keywords: Economic policy; Labor supply; Investments, Foreign; International cooperation; Income distribution